Surface modified nano copper powder and preparation method and application thereof
By modifying nanocopper powder with azide compounds, the problem of easy oxidation and agglomeration is solved, its dispersion and oxidation resistance are significantly improved, and the demand for high-density electronic interconnection is met.
Patent Information
- Application Number
- CN202411550959.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Due to its oxidation and agglomeration, nanocopper powder has poor dispersion in electronic interconnection applications and cannot meet the needs of high-density interconnection.
Azide compounds are used as surface modifiers, and combined with the surface of nanocopper powder through chemical bonds to form stable copper-azide functional bonds, improving the oxidation resistance and dispersion of nanocopper powder.
It significantly improves the oxidation resistance and dispersion of nano-copper powder, reduces its agglomeration trend, and enhances its application efficiency in electronic interconnected slurries and lubricating greases.
Smart Images

Figure CN119549698A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano metal powders, and in particular to a surface-modified nano copper powder and a preparation method and application thereof. Background Art
[0002] With the rapid development of AI (artificial intelligence) and the demand for huge computing power, high-performance computing chips are more integrated, and interconnections are multi-layered, especially the interconnections of HBM (high bandwidth memory) and high-density Z-direction PCB (printed circuit) boards, which put forward more stringent size and performance requirements for conductive materials. Copper powder is an important conductive material for electronic interconnection. The copper powder currently used is mainly micron powder, which cannot meet the needs of high-density interconnection. High-purity nano copper powder has excellent properties such as low sintering temperature, low softening temperature, high specific surface area, high electrical conductivity and thermal conductivity, and is a key material for the development of the next generation of electronic interconnection. However, since nano metals, especially nano copper powders, are very easy to oxidize and agglomerate, their practical applications are seriously affected. Therefore, it is necessary to solve the problems of oxidation and dispersion of high-purity nano copper powders. High-purity, nano-particle copper powder is a new type of low-melting point, high-conductivity key material for electronic interconnection, which can meet the needs of the electronic industry such as advanced high-density printed circuit board interconnection for high-performance conductive materials under complex working conditions.
[0003] Patent Publication No. CN101011747A discloses a method for manufacturing copper powder and copper powder. Under the action of protective colloid, water-soluble copper salt is added to make cuprous oxide mixed with a reducing agent. The copper powder manufacturing method prepares copper powder with a purity of 99.9% and a particle size distribution of 0.2-1 μm, but its size is still large; Patent Publication No. CN102896322A, CN101608077A and other disclosed methods for preparing nano copper powder, the size is controlled at 20-100, 20-70nm, but its purity is low; Patent Publication No. CN111975011A discloses a nano copper slurry, the particle size of its copper powder is bimodal distribution (large particles 120-200nm, small particles 5-20nm), resulting in too high sintering temperature (260-300°C). Nano copper powder is very easy to oxidize and has poor dispersibility (i.e., easy to agglomerate). Studies have shown that highly purified nano metals have excellent antioxidant properties. Patent Publication No. CN106479599A discloses surface-modified flaky nano-copper, which uses stearic acid, stearate, oleic acid and DDP to modify the surface of flaky nano-copper powder, and the size is 10-20 nm. However, the additives are too many and complicated, and only for flaky samples, and no mention is made for spherical powders with larger surface areas and higher modification difficulty. In addition, there is no modification of nano-copper powder with specific functional group organic matter, so it is urgent to obtain nano-copper powder and preparation method with both antioxidant properties and excellent dispersion. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a surface-modified nano copper powder and a preparation method and application thereof, which can simultaneously have excellent antioxidant properties and dispersibility.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a surface-modified nano copper powder, comprising nano copper powder and a surface modifier uniformly distributed on the outer surface of the nano copper powder matrix, wherein the nano copper powder and the surface modifier are bonded by chemical bonds, and the surface modifier is an azide compound.
[0007] Furthermore, the azide compound is a non-acidic organic compound containing an azide functional group, including ethyl azidoacetate, azido-PEG4-amine, 3-azidopropylamine, and azido-PEG-amine.
[0008] Furthermore, the original particle size of the nano copper powder is 5 to 500 nm, and the purity is greater than 99.99%.
[0009] Furthermore, the original particle size of the nano copper powder is 10 to 200 nm.
[0010] Furthermore, the particle size of the surface-modified nano-copper powder is smaller than the original particle size of the nano-copper powder, and the particle size of the surface-modified nano-copper powder is 5 to 200 nm, preferably 5 to 100 nm, and more preferably 5 to 50 nm.
[0011] Furthermore, the preparation method of the nano copper powder includes liquid phase reduction method, atomization method, electrodeposition method and physical vapor deposition method, preferably liquid phase reduction method.
[0012] Furthermore, the preparation process of the liquid phase reduction method is: adding sodium hydroxide-ethylene glycol solution to polyvinyl pyrrolidone-copper salt-ethylene glycol solution, controlling the pH at 8-11, and mixing evenly to obtain a precursor solution; placing it in a high-pressure reactor, heating it to 120-140°C, stirring at a speed of 300-800r / min, and a hydrogen pressure of 1-5MPa, reacting for 1-10h, and obtaining an ethylene glycol solution containing nano copper powder, and the solid matter separated by centrifugation is nano copper powder. Ethylene glycol as an organic solvent can be replaced by other common organic solvents.
[0013] Furthermore, the prepared nano copper powder is washed with anhydrous ethanol or acetone.
[0014] Furthermore, the concentration of the alkali metal organic solution is 0.1-0.5 mol / L, the mass ratio of polyvinyl pyrrolidone, copper salt and ethylene glycol in the polyvinyl pyrrolidone-copper salt-ethylene glycol solution is 10-30:0.1-0.5:20-60, and the copper salt is copper sulfate pentahydrate.
[0015] Furthermore, the ultrasonic treatment time is 3 to 5 minutes, the rotation speed of the centrifugal separation is 6500 r / min to 9200 r / min, and the centrifugal separation time is 3 to 20 minutes.
[0016] Furthermore, the molar ratio of the nano copper powder to the surface modifier is 1:(1-8).
[0017] Furthermore, the relevant parameters of the electrodeposition method are: current of 2 to 8A, voltage of 15 to 25V, duty cycle of 10% to 30%, power-on time of 1 to 10 minutes, and nano copper powder with a purity of 99.99% and a size of 155-300nm is obtained.
[0018] The second technical solution of the present invention is to provide a method for preparing surface-modified nano copper powder, comprising the following steps:
[0019] Adding the nano copper powder dispersion to the surface modifier solution while stirring, stirring until the mixture is uniform, and then continuing to stir to allow the nano copper powder and the azide functional group of the surface modifier to undergo a complex reaction to form a coordination bond, and after the reaction is completed, obtaining the solid matter by centrifugation or filtration;
[0020] The solid matter is freeze-dried and sealed to obtain a surface-modified nano copper powder product;
[0021] The surface modifier is an azide compound.
[0022] Furthermore, the nano copper powder dispersion liquid disperses the nano copper powder in an organic solvent, and the organic solvent includes anhydrous ethanol or acetone;
[0023] Furthermore, the concentration of the surface modifier is (3-20)×10 -5 mol / L, the solute is an azide compound, and the solvent is anhydrous ethanol.
[0024] Furthermore, the molar ratio of the nano-copper powder in the nano-copper powder dispersion to the surface modifier in the surface modifier solution is 1:(1-8).
[0025] Furthermore, the temperature for the reaction between the nano copper powder and the azide functional group of the surface modifier is room temperature, and the reaction time is 0.5 to 6 hours.
[0026] Furthermore, the nano copper powder is cleaned with anhydrous ethanol or acetone before use, and the cleaning method adopts ultrasound and centrifugation commonly used in the art.
[0027] Furthermore, the freeze-drying treatment temperature is -50 to -30°C, and the freeze-drying treatment time is 8 to 20 hours.
[0028] Furthermore, the sealed storage method is to store it in Ar, N2 or vacuum.
[0029] Furthermore, the solid matter is washed and then freeze-dried, and the washing solution includes anhydrous ethanol and water.
[0030] The third technical solution of the present invention is to provide an application of surface-modified nano copper powder, wherein the surface-modified nano copper powder is used for preparing electronic interconnection slurry and lubricating grease wear-resistant additive.
[0031] Furthermore, the sealed storage method is to store it in Ar, N2 or vacuum.
[0032] The third technical solution of the present invention is to provide an application of surface-modified nano copper powder, wherein the surface-modified nano copper powder is used to prepare copper powder for electronic interconnection paste and wear-resistant additive for lubricating grease.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] (1) The present invention introduces an azide compound with excellent activity and regulates its distribution on the surface of copper powder to form a stable copper-azide functional group bond, thereby effectively reducing the problem of easy agglomeration caused by the high free energy and surface area of the nano copper powder itself, and improving the surface purity of copper particles by controlling the purity of copper powder, thereby reducing the oxidation of the copper powder surface.
[0035] (2) The present invention modifies nano-copper powder by using azide compounds having different linking groups and containing azide functional groups as surface modifiers, and obtains nano-copper powder with excellent hydrophilicity or lipophilicity by regulating the hydrophilicity or lipophilicity of the linking groups (and different types of azide compounds). At the same time, the antioxidant and anti-agglomeration properties of the nano-copper powder are enhanced, and the dispersibility of the nano-copper powder in electronic interconnection slurries and lubricating greases is greatly improved, thereby improving the application efficiency of the electronic interconnection slurries or greases.
[0036] (3) The preparation method of the surface-modified nano-copper powder provided by the present invention is simple to operate, short in process, low in cost and has good modification effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The infrared spectra of the surface modified nano copper powder product of Example 1 and the unmodified nano copper powder and ethyl azidoacetate of Comparative Example 1;
[0038] Figure 2 This is a TEM image of the surface modified nano copper powder product of Example 1;
[0039] Figure 3 This is a TEM image of the surface modified nano copper powder product of Example 2;
[0040] Figure 4 The infrared spectra of the surface modified nano copper powder product of Example 3, the unmodified nano copper powder of Comparative Example 1 and azido-PEG-4;
[0041] Figure 5 The thermogravimetric analysis diagram of the unmodified nano copper powder of comparative example 1 and the surface modified nano copper powder of example 7;
[0042] Figure 6 TEM image of the unmodified nano copper powder of Comparative Example 1;
[0043] Figure 7 TEM image of the unmodified nano copper powder of Comparative Example 2;
[0044] Figure 8 The thermogravimetric analysis diagram of the unmodified nano copper powder of comparative example 3 and the surface modified nano copper powder of example 3;
[0045] Fig. 9 This is the TEM image of the unmodified nano copper powder of Comparative Example 2.
[0046] Fig.10 This is the SEM image of the unmodified nano copper powder of Comparative Example 3. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0048] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0049] In the following examples, the molecular formula of ethyl azidoacetate is C4H7N3O2, CAS No. 637-81-0, ≥95%; the molecular formula of azido-PEG-4 amine is C10H22N4O4, CAS No. 951671-92-4, ≥95%; the molecular formula of polyvinylpyrrolidone K30 is (C6H9NO) n , CAS No. 84057-81-8, 20% solution; the molecular formula of 3-azidopropylamine is C3H8N4, CAS No. 88192-19-2, ≥95%; the molecular formula of azido-PEG-amine is N3-PEG-NH2, ≥95%, MW2000Da. All were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0050] A surface modified nano copper powder comprises nano copper powder and a surface modifier uniformly distributed on the outer surface of a nano copper powder matrix, wherein the nano copper powder and the surface modifier are combined through chemical bonds, and the surface modifier is an azide compound.
[0051] As one of the preferred embodiments, the azide compound is a non-acidic organic compound containing an azide functional group, including ethyl azidoacetate, azido-PEG4-amine, 3-azidopropylamine, and azido-PEG-amine.
[0052] As one of the preferred implementations, the original particle size of the nano copper powder is 5 to 500 nm, and the purity is greater than 99.99%.
[0053] As one of the preferred implementations, the original particle size of the nano copper powder is 10 to 200 nm.
[0054] As one of the preferred implementations, the particle size of the surface modified nano copper powder is smaller than the original particle size of the nano copper powder, and the particle size of the surface modified nano copper powder is 5 to 200 nm, preferably 5 to 100 nm, and more preferably 5 to 50 nm.
[0055] As one of the preferred implementations, the preparation method of the nano copper powder includes liquid phase reduction method, atomization method, electrodeposition method and physical vapor deposition method, preferably liquid phase reduction method.
[0056] As one of the preferred embodiments, the preparation process of the liquid phase reduction method is: adding sodium hydroxide-ethylene glycol solution dropwise to polyvinyl pyrrolidone-copper salt-ethylene glycol solution, controlling the pH at 8-11, and mixing evenly to obtain a precursor solution; placing it in a high-pressure reactor, heating it to 120-140°C, stirring at a speed of 300-800r / min, and a hydrogen pressure of 1-5MPa, reacting for 1-10h to obtain an ethylene glycol solution containing nano copper powder, and the solid matter separated by centrifugation is nano copper powder. Ethylene glycol as an organic solvent can be replaced by other common organic solvents.
[0057] As one of the preferred implementations, the prepared nano copper powder is washed with anhydrous ethanol.
[0058] As one of the preferred embodiments, the concentration of the alkali metal organic solution is 0.1-0.5 mol / L, the mass ratio of polyvinyl pyrrolidone, copper salt and ethylene glycol in the polyvinyl pyrrolidone-copper salt-ethylene glycol solution is 10-30:0.1-0.5:20-60, and the copper salt is copper sulfate pentahydrate.
[0059] As one of the preferred implementations, the ultrasonic treatment time is 3 to 5 minutes, the rotation speed of the centrifugal separation is 6500 r / min to 9200 r / min, and the centrifugal separation time is 3 to 20 minutes.
[0060] As one of the preferred implementations, the molar ratio of the nano copper powder to the surface modifier is 1:(1-8).
[0061] As one of the preferred embodiments, the relevant parameters of the electrodeposition method are: current of 2 to 8A, voltage of 15 to 25V, duty cycle of 10% to 30%, power-on time of 1 to 10 minutes, and nano copper powder with a purity of 99.99% and a size of 155-300nm is obtained.
[0062] A method for preparing surface-modified nano copper powder comprises the following steps:
[0063] Adding the nano copper powder dispersion to the surface modifier solution while stirring, stirring until the mixture is uniform, and then continuing to stir to allow the nano copper powder and the azide functional group of the surface modifier to undergo a complex reaction to form a coordination bond, and after the reaction is completed, obtaining the solid matter by centrifugation or filtration;
[0064] The solid matter is freeze-dried and sealed to obtain a surface-modified nano copper powder product;
[0065] The surface modifier is an azide compound.
[0066] As one of the preferred implementations, the nano-copper powder dispersion is prepared by dispersing the nano-copper powder into an organic solvent, and the organic solvent includes anhydrous ethanol or acetone.
[0067] As one of the preferred embodiments, the concentration of the surface modifier is (3-20)×10 -5 mol / L, the solute is an azide compound, and the solvent is anhydrous ethanol.
[0068] As one of the preferred implementations, the molar ratio of the nano-copper powder in the nano-copper powder dispersion to the surface modifier in the surface modifier solution is 1:(1-8).
[0069] As one of the preferred embodiments, the temperature for the reaction between the nano copper powder and the azide functional group of the surface modifier is room temperature, and the reaction time is 0.5 to 6 hours.
[0070] As one of the preferred implementations, the nano copper powder is cleaned with anhydrous ethanol or acetone before use, and the cleaning method adopts ultrasound and centrifugation commonly used in the art.
[0071] As one of the preferred embodiments, the freeze-drying treatment temperature is -50 to -30°C, and the freeze-drying treatment time is 8 to 20 hours.
[0072] As one of the preferred embodiments, the sealed storage method is to store it in Ar, N2 or vacuum.
[0073] As one of the preferred implementations, the solid matter is washed and then freeze-dried, and the washing solution includes anhydrous ethanol and water.
[0074] The invention discloses an application of surface-modified nano copper powder, wherein the surface-modified nano copper powder is used for preparing electronic interconnection slurry and lubricating grease wear-resistant additive.
[0075] As one of the preferred embodiments, the sealed storage method is to store it in Ar, N2 or vacuum.
[0076] The invention discloses an application of surface-modified nano copper powder, wherein the surface-modified nano copper powder is used for preparing copper powder for electronic interconnection slurry and wear-resistant additive for lubricating grease.
[0077] Example 1
[0078] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0079] (1) Preparation of surface modifier organic solvent A:
[0080] 18 μL of ethyl azidoacetate was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0081] (2) Preparation of Nano Copper Powder:
[0082] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix well to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 130°C, stir it at a speed of 500r / min, and the hydrogen pressure is 2MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 10-50nm.
[0083] (3) Surface modification of nano copper powder:
[0084] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 200 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of nano-copper powder to ethyl azidoacetate was 1:8; stirring was continued for 0.5 h after the mixture was uniformly mixed, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 9200 r / min, the centrifugal time was 10 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0085] (4) Storage of surface modified nano copper powder products:
[0086] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 20 hours, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0087] Example 2
[0088] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0089] (1) Preparation of surface modifier organic solvent A:
[0090] 25 μL of ethyl azidoacetate was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0091] (2) Preparation of Nano Copper Powder:
[0092] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix well to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 140°C, stir it at a speed of 500r / min, and the hydrogen pressure is 2MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 30-50nm.
[0093] (3) Surface modification of nano copper powder:
[0094] 0.2 g of the washed nano-copper powder was placed in 200 mL of acetone to obtain a nano-copper powder dispersion (dispersion B), and 200 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of nano-copper powder to ethyl azidoacetate was 1:5.53; stirring was continued for 2 h after mixing until the mixture was uniform, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 9200 r / min, the centrifugal time was 10 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0095] (4) Storage of surface modified nano copper powder products:
[0096] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol and once with ultrapure water, freeze-dried at -40°C for 10 hours, and sealed with N2 to obtain a surface modified nano copper powder finished product.
[0097] Example 3
[0098] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0099] (1) Preparation of surface modifier organic solvent A:
[0100] 60 μL of azido-PEG-4 amine was placed in 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0101] (2) Preparation of Nano Copper Powder:
[0102] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix well to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 130°C, stir it at a speed of 500r / min, and the hydrogen pressure is 2MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 10-50nm.
[0103] (3) Surface modification of nano copper powder:
[0104] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 300 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of the nano-copper powder to the azido-PEG-4 amine was 1:4.77; stirring was continued for 1 hour after the mixture was uniformly mixed, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 8000 r / min, and the centrifugal time was 15 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0105] (4) Storage of surface modified nano copper powder products:
[0106] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 8h, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0107] Example 4
[0108] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0109] (1) Preparation of surface modifier organic solvent A:
[0110] 25 μL of 3-azidopropylamine was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0111] (2) Preparation of Nano Copper Powder:
[0112] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix evenly to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 130°C, stir it at a speed of 500r / min, and the hydrogen pressure is 1.5MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 30-100nm.
[0113] (3) Surface modification of nano copper powder:
[0114] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 300 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of the nano-copper powder to 3-azidopropylamine was 1:5.6; stirring was continued for 1 h after the mixture was uniformly mixed, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 8000 r / min, and the centrifugal time was 15 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0115] (4) Storage of surface modified nano copper powder products:
[0116] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 10 hours, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0117] According to the measurement, the finished product of surface modified nano copper powder has excellent dispersibility, no surface oxidation, and a particle size of 15 to 25 nm.
[0118] Example 5
[0119] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0120] (1) Preparation of surface modifier organic solvent A:
[0121] 25 μL of azido-PEG-amine was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0122] (2) Preparation of Nano Copper Powder:
[0123] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix evenly to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 130°C, stir it at a speed of 500r / min, and the hydrogen pressure is 1.5MPa. React for 3.5h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 30-100nm.
[0124] (3) Surface modification of nano copper powder:
[0125] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 300 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of the nano-copper powder to 3-azidopropylamine was 1:5.6; stirring was continued for 1 h after the mixture was uniformly mixed, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 8000 r / min, and the centrifugal time was 15 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0126] (4) Storage of surface modified nano copper powder products:
[0127] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 10 hours, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0128] According to the measurement, the finished product of surface modified nano copper powder has excellent dispersibility, no surface oxidation, and a particle size of 15 to 25 nm.
[0129] Example 6
[0130] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0131] (1) Preparation of surface modifier organic solvent A:
[0132] 25 μL of 3-azidopropylamine was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0133] (2) Preparation of Nano Copper Powder:
[0134] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix evenly to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 120°C, stir it at a speed of 500r / min, and the hydrogen pressure is 1.5MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 8-50nm.
[0135] (3) Surface modification of nano copper powder:
[0136] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 300 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of the nano-copper powder to 3-azidopropylamine was 1:5.6; stirring was continued for 1 h after the mixture was uniformly mixed, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 6500 r / min, and the centrifugal time was 20 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0137] (4) Storage of surface modified nano copper powder products:
[0138] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 10 hours, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0139] According to the measurement, the finished product of surface modified nano copper powder has excellent dispersibility, no surface oxidation, and a particle size of 5 to 25 nm.
[0140] Example 7
[0141] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0142] (1) Preparation of surface modifier organic solvent A:
[0143] 250 μL of ethyl azidoacetate was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0144] (2) Preparation of Nano Copper Powder:
[0145] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix well to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 130°C, stir it at a speed of 500r / min, and the hydrogen pressure is 2MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 10-50nm.
[0146] (3) Surface modification of nano copper powder:
[0147] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 100 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of nano-copper powder to ethyl azidoacetate was 1:1; stirring was continued for 0.5 h after mixing until the mixture was uniform, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 8500 r / min, the centrifugal time was 10 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0148] (4) Storage of surface modified nano copper powder products:
[0149] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 10 hours, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0150] Example 8
[0151] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0152] (1) Preparation of surface modifier organic solvent A:
[0153] 8 μL of ethyl azidoacetate was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0154] (2) Preparation of Nano Copper Powder:
[0155] Nano copper powder with a copper purity of 99.99% and a particle size of 52-103 nm purchased from Shanghai Maoguo Nanotechnology Co., Ltd. was taken and the nano copper powder was washed with anhydrous ethanol for 3 times.
[0156] (3) Surface modification of nano copper powder:
[0157] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 200 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of nano-copper powder to ethyl azidoacetate was 1:1; stirring was continued for 0.5 h after mixing until the mixture was uniform, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 8500 r / min, the centrifugal time was 10 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0158] (4) Storage of surface modified nano copper powder products:
[0159] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 10 hours, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0160] According to the measurement, the surface modified nano copper powder has good dispersibility and the copper powder particle size is 43-85nm.
[0161] Example 9
[0162] The present invention provides a surface-modified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0163] (1) Preparation of surface modifier organic solvent A:
[0164] 50 μL of ethyl azidoacetate was added to 20 ml of anhydrous ethanol and stirred for 10 min to obtain solution A.
[0165] (2) Preparation of Nano Copper Powder:
[0166] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix well to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 130°C, stir it at a speed of 500r / min, and the hydrogen pressure is 2MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 10-50nm.
[0167] (3) Surface modification of nano copper powder:
[0168] 0.2 g of the washed nano-copper powder was placed in 200 mL of anhydrous ethanol to obtain a nano-copper powder dispersion (dispersion B), and 150 mL of dispersion B was gradually added to solution A while stirring at a rate of 300 r / min, wherein the molar ratio of nano-copper powder to ethyl azidoacetate was 1:3; stirring was continued for 0.5 h after the mixture was uniformly mixed, so that the nano-copper powder and the azide functional group of the surface modifier underwent a complex reaction to form a coordination bond, and centrifuged after the reaction was completed, the centrifugal speed was 8500 r / min, and the centrifugal time was 10 min, and a solid surface-modified nano-copper powder semi-finished product was obtained by separation.
[0169] (4) Storage of surface modified nano copper powder products:
[0170] The surface modified nano copper powder semi-finished product was washed twice with anhydrous ethanol, washed once with ultrapure water, freeze-dried at -40°C for 10 hours, and sealed with Ar to obtain a surface modified nano copper powder finished product.
[0171] Comparative Example 1
[0172] This comparative example provides an unmodified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0173] (1) Preparation of nano copper powder:
[0174] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix well to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 130°C, stir it at a speed of 500r / min, and the hydrogen pressure is 2MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 10-50nm.
[0175] (2) The cleaned nano-copper powder was washed twice with anhydrous ethanol and once with ultrapure water, freeze-dried at -40°C for 10 h, and sealed with Ar to obtain unmodified nano-copper powder.
[0176] Comparative Example 2
[0177] This comparative example provides an unmodified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0178] (1) Preparation of nano copper powder:
[0179] Dissolve 10g of polyvinyl pyrrolidone K30 and 0.3g of copper sulfate pentahydrate in 40g of ethylene glycol to obtain a polyvinyl pyrrolidone-copper salt-ethylene glycol solution; dissolve sodium hydroxide in ethylene glycol to obtain a 0.1mol / L sodium hydroxide-ethylene glycol solution, take 35mL of sodium hydroxide-ethylene glycol solution and drop it into the above polyvinyl pyrrolidone-copper salt-ethylene glycol solution, mix evenly to obtain a precursor solution. Place it in a high-pressure reactor, heat it to 120°C, stir it at a speed of 500r / min, and the hydrogen pressure is 2MPa. React for 3h to obtain an ethylene glycol solution containing nano copper powder, centrifuge it, and the solid substance obtained is nano copper powder, and then wash the solution 3 times with anhydrous ethanol. The copper purity of the prepared nano copper powder is 99.99%, and the particle size is 41-85nm.
[0180] (2) The cleaned nano-copper powder was washed twice with anhydrous ethanol and once with ultrapure water, freeze-dried at -40°C for 10 h, and sealed with Ar to obtain unmodified nano-copper powder.
[0181] Comparative Example 3
[0182] This comparative example provides an unmodified nano copper powder and a preparation method thereof, wherein the preparation method comprises the following steps:
[0183] (1) Preparation of nano copper powder:
[0184] Nano copper powder was prepared by electrodeposition with a current of 5A, a voltage of 20V, a duty cycle of 20%, and a power-on time of 5min. Nano copper powder was obtained with a purity of 99.99% and a size of 155-300nm.
[0185] (2) The cleaned nano-copper powder was washed twice with anhydrous ethanol and once with ultrapure water, freeze-dried at -40°C for 10 h, and sealed with Ar to obtain unmodified nano-copper powder.
[0186] The surface modified nano copper powder obtained in Example 1 and the unmodified nano copper powder in Comparative Example 1 were analyzed by infrared spectroscopy. Figure 1 As shown in the figure, it can be seen that the surface modified nano copper powder finished product is compared with the unmodified nano copper powder at 3400cm -1 An obvious peak appeared at the 40°C, indicating that the copper atoms on the surface of the copper powder were linked with ethyl azidoacetate to form a stable bond.
[0187] Figure 2 This is the TEM image of the finished surface-modified nano-copper powder of Example 1. It can be seen that the copper powder surface is linked to the azide functional group, which reduces its specific surface area and agglomeration effect, and no large agglomerated particles are formed, and the particle size is 10 to 30 nm.
[0188] Figure 3 This is the TEM image of the finished surface-modified nano-copper powder of Example 2. It can be seen that the copper powder surface is linked to the azide functional group, which reduces its specific surface area and agglomeration effect, and no large agglomerated particles are formed, and the particle size is 10 to 20 nm.
[0189] The surface modified nano copper powder obtained in Example 3, the unmodified nano copper powder and azido-PEG-4 in Comparative Example 1 were subjected to infrared spectroscopy analysis. The results are as follows: Figure 4 As shown in the figure, the surface modified nano copper powder finished product is compared with the unmodified nano copper powder at 3400cm -1An obvious peak appears at , indicating that the copper atoms on the surface of the copper powder are linked to the azido-PEG-4 amine to form a stable bond. Example 3 The surface-modified nano-copper powder product modified with azido-PEG-4 amine has certain anti-oxidation and anti-agglomeration capabilities.
[0190] Thermogravimetric analysis was performed on the unmodified nano copper powder of comparative example 1 and the surface modified nano copper powder of example 7. The results are as follows: Figure 5 As shown, the weight loss of the surface modified nano copper powder of Example 7 with increasing temperature is smaller than that of the original copper powder, indicating that the copper powder surface modified with azide compounds has the same antioxidant properties.
[0191] The unmodified nano copper powder of Comparative Example 1 was photographed under a transmission electron microscope. Figure 6 As shown by Figure 6 It can be seen that the particle size of the unmodified nano copper powder is 10-50nm.
[0192] Figure 7 This is the TEM image of the unmodified nano copper powder of Comparative Example 2. It can be seen that the original copper powder without surface modification has particles agglomerated with each other, resulting in poor dispersibility and overlapping particles. Therefore, the size of the copper powder is also relatively large. The copper powder particles are 41-85nm, which is larger than 40nm.
[0193] Thermogravimetric analysis was performed on the unmodified nano copper powder of comparative example 3 and the surface modified nano copper powder of example 3. The results are as follows: Figure 8 As shown, the weight loss of the surface modified nano copper powder product with increasing temperature is smaller than that of the original copper powder, indicating that the copper powder surface modified with azide compounds has the same antioxidant property. Therefore, the nano copper powder modified with azide PEG-4 amine has certain antioxidant and anti-agglomeration capabilities.
[0194] Fig. 9 This is a TEM image of the unmodified nano-copper powder of Comparative Example 2. It can be seen that the particle size of the unmodified nano-copper powder of Comparative Example 2 is greater than 40 nm.
[0195] Fig.10 This is a SEM picture of unmodified electrodeposited nano-copper powder. It can be seen that the unmodified copper powder particles are agglomerated with each other, especially the small particles are agglomerated.
[0196] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A surface-modified nano copper powder, characterized in that: The invention comprises nano copper powder and a surface modifier which is evenly distributed on the outer surface of the nano copper powder matrix. The nano copper powder and the surface modifier are combined by chemical bonds, and the surface modifier is an azide compound.
2. A surface-modified nano copper powder according to claim 1, characterized in that: The azide compound is a non-acidic organic compound containing an azide functional group, including ethyl azidoacetate, azido-PEG4-amine, 3-azidopropylamine, and azido-PEG-amine.
3. A surface-modified nano copper powder according to claim 1, characterized in that: The original particle size of the nano copper powder is 5-500nm, and the purity is greater than 99.99%.
4. A surface-modified nano copper powder according to claim 1, characterized in that: The molar ratio of the nano copper powder to the surface modifier is 1:(1-8).
5. The surface-modified nano copper powder according to claim 1, characterized in that: The particle size of the surface modified nano copper powder is smaller than the original particle size of the nano copper powder, and the particle size of the surface modified nano copper powder is 5 to 200 nm.
6. The method for preparing a surface-modified nano copper powder according to any one of claims 1 to 5, characterized in that: The following steps are involved: Adding the nano copper powder dispersion to the surface modifier solution while stirring, stirring until the mixture is uniform, and then continuing to stir to allow the nano copper powder and the azide functional group of the surface modifier to undergo a complex reaction to form a coordination bond, and after the reaction is completed, obtaining the solid matter by centrifugation or filtration; The solid matter is freeze-dried and sealed to obtain a surface-modified nano copper powder product; The surface modifier is an azide compound.
7. The method for preparing a surface-modified nano copper powder according to claim 6, characterized in that: The nano copper powder dispersion liquid disperses the nano copper powder in an organic solvent, and the organic solvent includes anhydrous ethanol or acetone; The concentration of the surface modifier is (3-20)×10 -5 mol / L, the solute is an azide compound, and the solvent is anhydrous ethanol.
8. The method for preparing a surface-modified nano copper powder according to claim 6, characterized in that: The molar ratio of the nano copper powder in the nano copper powder dispersion to the surface modifier in the surface modifier solution is 1:(1-8).
9. The method for preparing a surface-modified nano copper powder according to claim 6, characterized in that: The temperature for the reaction between the nano copper powder and the azide functional group of the surface modifier is room temperature, and the reaction time is 0.5 to 6 hours.
10. The use of a surface-modified nano copper powder according to any one of claims 1 to 5, characterized in that: The surface modified nano copper powder is used for preparing electronic interconnection slurry and lubricating grease wear-resistant additive.
Citation Information
Patent Citations
Method of producing copper powder and copper powder
CN101011747A
Nano-copper conductive ink preparation method
CN101608077A
Preparation method for nano-copper with oxidation resistance and dispersibility
CN102896322A
Surface-modified flaky nanometer copper and lubricating oil containing surface-modified flaky nanometer copper
CN106479599A
Nanometer copper paste for chip pressureless sintering interconnection and preparation method and application thereof
CN111975011A